Lionel asbo ebook State of england. - Amis, Martin (2012)
By turns outrageous and touching, an exuberant Dickensian satire of crime, celebrity, and modern culture from "one of the most gifted novelists of his generation” ( TIME ) “One of Amis’s funniest novels.” — The New Yorker Des Pepperdine is a boy out of place. He lives on the thirty-third floor of a London housing project; while his peers pick fights, Des retreats to the public library. What’s more, Des’s uncle and guardian, Lionel Asbo, is one of the most notorious petty criminals in the city. Yet Lionel, full of inept devotion to his nephew, dutifully teaches Des the essentials of becoming a man (always carry a knife; pornography is easier than dating; pit bulls should be fed Tabasco sauce). To survive these lessons, Des seeks solace in a covert romantic union that would fill Lionel with rage. But just as Des begins to lead a healthier life, Lionel wins £140 million in the lottery. The money ushers in a public-relations firm for Lionel, along with a cannily ambitious topless model–poet. Through it all, Lionel remains his vicious, oddly loyal self, and his problems, as well as Des’s, only seem to multiply.